MANAJEMEN RISIKO SISTEM INFORMASI STUDENT SERVICE CENTER MENGGUNAKAN METODE OCTAVE ALLEGRO - Ito Setiawan; Riyanto Riyanto; Ika Romadoni Yunita; Jeffri Prayitno Bangkit Saputra (JURNAL REKAYASA INFORMASI, 2023)
Amikom Purwokerto University provides services to students in the form of a student service center system that is used for student academic management. The system contains general, academic, events, library, student activities, learning processes, financial and other menus. The problem that often occurs in student service centers is the frequent occurrence of server errors when filling in online KRS which results in many students getting random classes so their schedules collide. This study has the aim of analyzing threats, conducting assessments and evaluating risks that occur to campus assets. OCTAVE Allegro is a method used to analyze existing problems. The results of the study are that there are 3 areas of concern. There are 4 Impact Areas Prioritization in priority order of reputation, productivity, finance and security. In the area of ​​concern for exploiting system security holes, there are 5 mitigations. In terms of storage space capacity, there are 3 mitigations and unstable internet parts, there are 4 mitigations. From the results of the risk analysis, the highest value is 28, which is an unstable internet area of ​​concern in the system used